Implementasi Fungsi Manajemen Keuangan Sekolah dan Implikasinya pada Kualitas Pendidikan: Study Kasus SMP Lab School Universitas Negeri Surabaya (UNESA) - Yuliana Harry Rahmawati; Dewie Tri Wijayati Wardoyo; Amrozi Khamidi (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to describe the implications of the education financial management function on the quality of education at UNESA Labschool Middle School. Research with a qualitative approach uses a qualitative descriptive method. The research was conducted at UNESA Labschool 2 Middle School which is located in the UNESA Ketintang Surabaya Campus complex and UNESA Lab School 3 on Jl. Raya UNESA Tongue Wetan Surabaya. The primary data in this study are informants. Secondary data in the form of documents collected through informants. sources of data obtained are documents, participatory observation, and in-depth interviews. Data collection techniques with the method of observation, interviews and documentation. Data analysis was carried out through several steps, namely data reduction, data display, and conclusion drawing or verification. The results of the study show that financial management is oriented towards the independence of an organization or institution, in this case Labschool Middle School with implications for Teachers, Teachers get material well-being in the form of adequacy of allowances for daily living expenses and spiritual well-being in the form of security and comfort in carrying out daily activities -days in the neighborhood. The implications for students are channeling students' talents and interests through self-development activities in extracurricular activities that increase student achievement. The implications of implementing the proper financial management function will have an impact on the quality of education within the UNESA Labschool Middle School.